An evaluation of Global Zakat Game (GZG) as edutainment board game in enhancing Zakat education in Malaysia - Ab. Rahman, Azman; Sahrir, Muhammad Sabri; Zainuddin, Nurkhamimi; Abd. Khafidz, Hasanah (Academic Journals, 2018)
Board games have become one of the useful tools in teaching and learning. Many instructors and educators have chosen to use board games to enhance the way of delivering course contents. A board game will help students understand the education concept quickly and get involved in experiential learning, where students can manage and solve problems in an actual situation. This study will focus on the evaluation of a board game, namely Global Zakat Game (GZG) as a Zakat edutainment tool among users at various levels of learning institutions in Malaysia. The respondents were purposively selected among a Malaysian national competition in using Global Zakat Game (GZG) organized at Islamic Science University of Malaysia (USIM) on 8 November 2017. A questionnaire was distributed among 235 participants from various levels of learning institutions during the national event to evaluate the practical use of GZG as a Zakat edutainment tool in increasing their comprehension and understanding on Zakat theories and concepts. The result indicated that the use of GZG as a Zakat edutainment tool has a positive impact on users and players as it helps them to learn more about Zakat theories and concepts between high (4.65) and moderate high (3.95) mean scores. Most of the respondents mentioned that they enjoyed playing GZG as it involves experiential learning. It also can be used as an edutainment tool for learners and society at all ages.